P‐42: Visibility Analysis in Vehicle Rear Mirror OLED using Fourier Optics. Issue 1 (29th May 2019) - Park, Ju-Un; Jang, Hun; Lee, Chan-Ho; Jeong, Young-Min; Lee, Won-Ho; Kim, Eui-Tae; Kim, Chang-Soo; Kim, Jae-Hong; Jun, Myung-Chul; Kang, In-Byeong
Abstract : When mirror OLED is used as a rear mirror for a vehicle, it is seen that the headlights of the rear vehicle spreads and the reflective visibility is lowered. Prior to improving the degraded visibility, we first defined the visibility of reflective display and developed a visibility simulator using Fourier optical analysis.